Effects of exogenous lactic acid bacteria and maize meal on fermentation quality and microbial community of Orychophragmus violaceus silage - Zheng, Mingli; Mao, Peichun; Tian, Xiaoxia; Meng, Lin (Frontiers in Microbiology, 2023)
Orychophragmus violaceus is a local Brassicaceae in China, while most of it is directly mowed and discarded after the ornamental period. In order to develop forage resources, this study firstly evaluated the potential preservation of O. violaceus silage. O. violaceus was harvested at full-bloom stage, and ensiled without (CK) or with maize meal (Y5), lactic acid bacteria inoculant (Z) and compound additive (Y5Z) for 60 d. Results of chemical and microbiological analysis showed that a large amount of lactic acid was produced and the final pH value was below 4.1 in silages regardless of additive application. CK silage was well preserved as indicated by the low levels of dry matter loss and butyric acid content, and the predominant genus were identified as Enterococcus and Pediococcus. Y5 silage had potential health risks for humans and animals as seen by frequent occurrence of pathogenic bacteria Clostridium and Achromobacter. Z and Y5Z silages were poorly preserved, resulting in great dry matter loss and butyric acid content. Considering the abundant acetic acid production, the dominant Lactobacillus might possess a heterofermentative pathway in Z and Y5Z silages. In conclusion, O. violaceus has the potential to be long stored as silage because of its sufficient water-soluble carbohydrates, while exogenous lactic acid bacteria and maize meal generally provided little positive effect. In future research, efficient homofermentative Lactobacillus strains were suggested to be screened to further enhance the ensiling process of O. violaceus silage.